2020
DOI: 10.1002/jper.19-0470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐22 on osteogenic differentiation and the osteoclastogenic response of human periodontal ligament fibroblasts in vitro

Abstract: BackgroundInterleukin‐22 (IL‐22) exerts extensive biological effects, playing both protective and pathological roles in autoimmune and infectious diseases. However, the specific role and mechanism of IL‐22 in the pathogenesis of periodontitis have not been clarified. The aim of this study was to analyze the possible roles of IL‐22 in the osteoclastogenesis and osteogenesis of periodontitis.MethodsHuman periodontal ligament fibroblasts (hPDLFs) were treated with IL‐22 and/or lipopolysaccharide from Porphyromona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…IL-22 has been reported to accelerate bone degradation in arthritis, , and IL-22-expressing T cells have been indicated to mediate alveolar bone resorption . On the contrary, it has been shown that IL-22 induces osteogenic differentiation of mesenchymal stem cells and periodontal ligament fibroblasts . Different disease models and different progenitor cells studied may have contributed to the inconsistency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-22 has been reported to accelerate bone degradation in arthritis, , and IL-22-expressing T cells have been indicated to mediate alveolar bone resorption . On the contrary, it has been shown that IL-22 induces osteogenic differentiation of mesenchymal stem cells and periodontal ligament fibroblasts . Different disease models and different progenitor cells studied may have contributed to the inconsistency.…”
Section: Resultsmentioning
confidence: 99%
“…67 On the contrary, it has been shown that IL-22 induces osteogenic differentiation of mesenchymal stem cells 68 and periodontal ligament fibroblasts. 69 Different disease models and different progenitor cells studied may have contributed to the inconsistency. Analysis of our data showed that HAp-100 induced the largest increase of IL-22 and produced the best osteogenic impact in injured mouse mandibles, pointing to a positive role of IL-22 in bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Th22 lymphocytes have also been described as an osteoclastogenic T helper subset (54). Similar to IL-17, IL-22 can directly promote osteoclast differentiation (54) and induce RANKL expression in periodontal ligament fibroblasts (55). Our results showed that components of the periodontal immune cell compartment are able to detect changes in the structure of O-PS from the A. actinomycetemcomitans LPS, which resulted in the modification of the local immune response mediated by the Th1, Th17, and Th22 lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…116 They established that the optimized HAp nanorods could result in a greater production of IL-22 from T cells, thereby inducing the osteogenic differentiation of BMSCs and PDLCs via the JAK/STAT3 pathway. 116,117…”
Section: Introductionmentioning
confidence: 99%